2016
DOI: 10.1007/s00425-016-2632-1
|View full text |Cite
|
Sign up to set email alerts
|

Differences in photosynthetic responses of NADP-ME type C4 species to high light

Abstract: Main conclusion Three species chosen as representatives of NADP-ME C4 subtype exhibit different sensitivity toward photoinhibition, and great photochemical differences were found to exist between the species. These characteristics might be due to the imbalance in the excitation energy between the photosystems present in M and BS cells, and also due to that between species caused by the penetration of light inside the leaves. Such regulation in the distribution of light intensity between M and BS cells shows th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 71 publications
1
4
0
Order By: Relevance
“…This is validated herein, where 100 mM NaCl induced the activity of NADP-ME to be several folds higher; this may indicate light sensitization, however, under a saturated malate concentration. Therefore, the activity of NADP-ME would be complimented by light-induced redox changes, -SH/-S-S-, as well as under alkalinity [36]. Polymorphic gene expression for NADP-ME, as deduced through in-gel activity staining, also confirmed the light-induced NaCl sensitivity in the present experiment.…”
Section: Discussionsupporting
confidence: 78%
“…This is validated herein, where 100 mM NaCl induced the activity of NADP-ME to be several folds higher; this may indicate light sensitization, however, under a saturated malate concentration. Therefore, the activity of NADP-ME would be complimented by light-induced redox changes, -SH/-S-S-, as well as under alkalinity [36]. Polymorphic gene expression for NADP-ME, as deduced through in-gel activity staining, also confirmed the light-induced NaCl sensitivity in the present experiment.…”
Section: Discussionsupporting
confidence: 78%
“…In this way, the C4 photosynthetic metabolism operates a CO 2 -concentrating mechanism around Rubisco, which in turn significantly reduces the Rubisco oxygenase activity. In addition, BSC chloroplasts contain low level of PSII (Romanowska et al, 2017) and, although in BSC chloroplasts PSII contains all polypeptides involved in electron transport and oxygen evolution, it is largely inactive (Romanowska et al, 2008). In contrast, MC chloroplasts have higher PSII activity but practically absent Rubisco activity (Furbank and Foyer, 1988).…”
Section: Photoinhibition In C3 and C4 Speciesmentioning
confidence: 99%
“…us, PSII in BS agranal chloroplasts is not equivalent to PSII in the stromal membranes of C3 plants. (Romanowska et al, 2017). ese differences might be due to the imbalance in the excitation energy between the photosystems present in the M and BS cells and the differences in the penetration of light inside the leaves.…”
Section: Structure and Function Of Photosystem II In Agranal Maize Bu...mentioning
confidence: 99%
“…It was found that the non-radiative dissipation of energy in the studied plants was not dependent on carotenoid content, and the activity of the antioxidant enzymes and the malondialdehyde and H 2 O 2 levels were similar. is suggests that other photoprotective mechanism(s) might have been involved in NADP-ME species under high light stress (Romanowska et al, 2017).…”
Section: Structure and Function Of Photosystem II In Agranal Maize Bu...mentioning
confidence: 99%